Decentralized design of interconnected H[the sign of infinity] feedback control systems with quantized signals - Zhai, Guisheng; Chen, Ning; Gui, Weihua (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we consider the design of interconnected H[the sign of infinity] feedback control systems with quantized signals. We assume that a decentralized dynamic output feedback has been designed for an interconnected continuous-time LTI system so that the closed-loop system is stable and a desired H? disturbance attenuation level is achieved, and that the subsystem measurement outputs are quantized before they are passed to the local controllers.
Keywords: interconnected systems; decentralized H[the sign of infinity] control; dynamic output feedback; quantizer; quantization; matrix inequality; LMI